Relações entre mães e filhas em contexto de violência doméstica e o impacto na diferenciação do self: um olhar sob uma perspectiva intergeracional - Ferreira, Luciana (2022)
Motherhood is immersed in idealized images of love, perfection, goodness, among other positive adjectives. However, we observed in clinical practice in certain cases, conflicts in this relationship. The present research aimed to analyze these conflictual relations, from the daughter’s perspective, with regard to the impact on the process of differentiation of the self of the child. In a therapeutic process, it was possible to observe the suffering of daughters from problematic relationships with their mothers, who aroused interest in understanding this phenomenon. To this end, we used the qualitative research method, delineated through the study of multiple cases and developed with the use of semi-structured interviews, genogram and timeline. The analysis of information took place through the codification of information, and the interpretation by a look that relegated the intergenerational transmission of patterns, because from a systemic perspective we recognize that symptomatic behaviors are constituted by their participation in circular patterns, which can self-perpetuate. We were surprised by gender domestic violence, as well as conflicts in the mother-daughter relationship. The results corroborate the literature and indicate that the conflictual relations permeated by intrafamily domestic violence have an impact on the differentiation process of daughters